Rapid identification of multiple supernumerary ring chromosomes with a new FISH technique. Issue 11 (November 1997) - Mackie-Ogilvie, C; Waddle, K; Mandeville, J; Seller, M J; Docherty, Z
Abstract : Multiple supernumerary ring chromosomes are a rare cytogenetic finding which is poorly understood. With the introduction of FISH techniques, their chromosomal origin can now be defined clearly. The techniques described previously are complicated and time consuming. We report a new rapid technique which has been used to investigate two new cases. Multiple probes were hybridised to a single slide by means of marking the underside with a diamond pen to form a grid of squares, pipetting fixed cell suspension into the centre of each square, forming a rubber solution grid on the denatured, dehydrated slide following the lines on the underside, adding a mixture of probes into each square, and sealing the slide with a silicone rubber rim and a covering slide. The type of probe and the size, dimensions, and number of squares in the grid can be tailored to individual cases. The two new cases examined here are mosaic for three (case 1) and four (case 2) supernumerary ring chromosomes derived from different chromosomes. Normal cell lines were also present. The karyotypes were established as 47, XY, +r(4)/47, XY, +r(17)/.../48, XY, +r(17), +r(20)/ 49, XY, +r(4), +r(17), +r(20)/46, XY for case 1 and 47, XX, +r(4)/47, XX, +r(8)/47, XX, +r (10)/48, XX, +r(X), +r(4)/... /49, XX, +r(X), +r (8), +r(10)/46, XX for case 2. Our findings suggest that the ring chromosomes were formed during meiosis, perhaps involving complex rearrangements, resulting in a germ cell containing all markers, with subsequent loss of markers during cell division. Our second case also shows that the outcome is not invariably mental or physical handicap.